Etika Komunikasi di Media Sosial Mahasiswa Mik di Stikes Santa Elisabeth Medan - Anastasya Nikita Br Sinuraya; Mitra Amelia Ndruru; Teddy Pratama Yamonaha Halawa (MUKASI: Jurnal Ilmu Komunikasi, 2024)
The presence of social media has had an impact on changes in human behavior and attitudes and communication. Through social media, information can be spread widely, freely and quickly. Users have greater freedom in selecting, producing and sharing messages on social media. This freedom demands ethical responsibility to users, including young people. This research explains the ethics of social medical communication for students at Mik Stikes Santa Elisabeth Medan. There are 15 people (15%) with good moral ethics because these respondents already know how to act morally ethically and are able to apply it in their daily lives. around 247 respondents) stated that they often utter dirty speech acts (words). Furthermore, 1.6% (4 respondents) stated that they sometimes said dirty words. the percentage was 23 students (56.4%) and the good criteria were 14 students (32.1%), the remaining 5 students with a percentage (11.5%) had very good communication ethics with teachers. To respond to the discomfort of digital communication users, researchers classify communication ethics into three things, including: 1. Digital communication ethics in the context of time, 2. Digital communication ethics in the context of age, 3. Digital communication ethics in the context of message content.